GREEN ECONOMY AS A GUARANTEE OF SUSTAINABLE DEVELOPMENT - Inna Tomashuk (Three Seas Economic Journal, 2022)
The purpose of the article is to analyze current trends in the concept of sustainable development in the world economy, taking into account new trends in the "green" economy and "greening" of the international financial system, which is the basis of "green" investment. Methodology. The work uses general and special methods and techniques of cognition: methods of theoretical generalization, analysis, synthesis and grouping, logical-historical method, deduction and induction. The strategic priorities of formation of new "green" directions of economy and ecological transformation of economy of existing branches are analyzed. It is proposed to find ways of further development based on the preservation of natural potential, which is associated with numerous benefits for the international community and all nations in terms of food, energy and water security and climate change. The priority formations of the state policy on the basis of introduction of innovative ecologically safe technologies which will be able to provide sustainable development of a society in strategic perspective are defined. The current trends in the implementation of the concept of sustainable development in the world economy are analyzed, with special attention to new trends in the "green" economy and "greening" of the international financial system, which is the basis of "green" investment. Results indicate that the transformation of the economy in the direction of ecology has laid the foundations for the concept of sustainable development. The “green” economy is the basis for the implementation of the concept of sustainable development on the basis of more efficient resource and energy consumption, reduction of CO2 emissions, reduction of harmful effects on the environment and development of a socially integrated society. Practical implications. "Greening" the economy requires "reformatting" current and future investments, additional costs beyond the usual approach. The UN Conference on Sustainable Development Rio + 20 in 2012 became a platform for the development of a "green" economy at the international level: the "green" economy has been officially recognized as an appropriate tool for promoting sustainable development. An obvious barrier to the development of "green" investment at the state level is the lack of quality of basic strategic documents on sustainable development and their practical effectiveness. In line with its commitments under the Paris Agreement and the Global Sustainable Development Goals (CSDs), international financial organizations, banking unions and institutions, as well as governments in most parts of the world, have begun to work actively for green finance. Value/originality. Green funding is seen today as funding for the “future”: the need to combine funding and meeting the CSDs. The contribution of business to environmental issues involves the commitment to compensate for environmental damage due to economic activities.